Intervensi Pemberdayaan Keluarga Dalam Penggunaan Obat Herbal Terhadap Pengobatan Gejala Tuberkulosis - Ro'isah; Laili, Nurul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Tuberculosis (TB) remains a public health problem. TB control programs involving the community have increased the detection of TB suspects, but these cases are not followed by treatment. The purpose of this study was to determine the effect of family empowerment on TB patient compliance.. Methods: This research is a pre-experimental research type. The population is all patients diagnosed with TB in Probolinggo Regency amounting to 35 people, the population is all families at risk of tuberculosis amounting to 30 heads of families, a sample of some families at risk of tuberculosis according to the inclusion and exclusion criteria amounting to 30 people, with a simple random sampling technique. Data collection using a questionnaire sheet before and after the intervention. Educational and training interventions were carried out in 1 meeting with 2 (two) sessions. Data were analyzed statistically with the help of SPSS paired T test. Results: The results of the study showed that knowledge was lacking 25 (83.3%), attitude was lacking 20 (66.7%) and skills were lacking in the use of herbal medicine 16 (53.3%) and after the intervention most of the knowledge was good 23 (76.7%), attitude was good 22 (73.3%) and skills were good 21 (70%) The results of the analysis showed the influence of family empowerment in the Use of Herbal Medicine on the Treatment of Tuberculosis symptoms (p.0.001 < α, 0.05)Conclusion: With the increase in knowledge, attitudes and skills of families in preventing tuberculosis, it is hoped that families can use herbal medicines for tuberculosis symptoms. Family empowerment, use of herbal tuberculosis medicine